2016
DOI: 10.18632/oncotarget.13302
|View full text |Cite
|
Sign up to set email alerts
|

The secretion and biological function of tumor suppressor maspin as an exosome cargo protein

Abstract: Maspin is an epithelial-specific tumor suppressor shown to exert its biological effects as an intracellular, cell membrane-associated, and secreted free molecule. A recent study suggests that upon DNA-damaging g-irradiation, tumor cells can secrete maspin as an exosome-associated protein. To date, the biological significance of exosomal secretion of maspin is unknown. The current study aims at addressing whether maspin is spontaneously secreted as an exosomal protein to regulate tumor/stromal interactions. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 73 publications
0
17
0
4
Order By: Relevance
“…It is well documented that normal breast epithelial cells MCF‐10A can form acini in three dimensional extracellular matrix (ECM) such as Matrigel. In an earlier study, we have reported the generation of MCF‐10A‐derived maspin knock‐ down stable clones [Dean et al, ]. In contrast to the acini formation by the parental MCF‐10A and scrambled siRNA‐transfected control (NC1), maspin knock‐down clones (siMas8 and siMas11) were more proliferative, formed disorganized cellular aggregates with increased infiltration into the Matrigel (Fig.…”
Section: Multifaceted Biological Functions Of Maspin In Mammary Glandmentioning
confidence: 91%
See 2 more Smart Citations
“…It is well documented that normal breast epithelial cells MCF‐10A can form acini in three dimensional extracellular matrix (ECM) such as Matrigel. In an earlier study, we have reported the generation of MCF‐10A‐derived maspin knock‐ down stable clones [Dean et al, ]. In contrast to the acini formation by the parental MCF‐10A and scrambled siRNA‐transfected control (NC1), maspin knock‐down clones (siMas8 and siMas11) were more proliferative, formed disorganized cellular aggregates with increased infiltration into the Matrigel (Fig.…”
Section: Multifaceted Biological Functions Of Maspin In Mammary Glandmentioning
confidence: 91%
“…Laboratory investigations further demonstrate that the multifaceted tumor suppressive activities of maspin may derive from its multiple sub‐cellular compartmentalization. Maspin can be secreted via dual non‐classical secretory pathways as both a soluble protein and as an exosomal cargo protein [Dean et al, ]. Soluble maspin has been shown to inhibit tumor cell invasion and motility [Sheng et al, , ; Zhang et al, ], increase cell adhesion to ECM [Bernardo et al, ], block tumor‐associated ECM degradation [Cher et al, ], and retard the detachment of cancer cells from established focal adhesion sites [Yin et al, ].…”
Section: Multifaceted Biological Functions Of Maspin In Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…After extraction, exosomes can be conveniently processed for physical characterization by means of Dynamic Light Scattering (DLS), Transmission Electron Microscopy (TEM), and Scanning Electron Microscopy (SEM) [50]. In the typical experimental procedure, the obtained exosome suspension, after isolation and physical characterization, may be homogenized.…”
Section: Detection Of Exosome Proteins As Biomarkers For Gastrointestmentioning
confidence: 99%
“…We have previously reported the existence of different maspin isoforms in the cell [16,22]. Maspin is found in different cellular compartments other than nucleus, including mitochondria [23], endoplasmic reticulum-associated vesicles [2], plasma membrane [24] and exosomes [25]. Therefore, maspin isoforms may be located in different compartments, implying a diverse regulation of subcellular localization.…”
Section: Gfp-maspinnlsmentioning
confidence: 99%